Preparation, analysis and toxicity characterisation of the redox metabolites of the azo food dye tartrazine - Ruth Pay; Abigail V. Sharrock; Riley Elder; Alaigne Maré; Joe Bracegirdle; Dan Torres; Niall Malone; Jan Vorster; Libusha Kelly; Ali Ryan; P. David Josephy; Emma Allen-Vercoe; et al. (Food and Chemical Toxicology, 2023)

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

UV hyper‐resistance in Prochlorococcus MED4 results from a single base pair deletion just upstream of an operon encoding nudix hydrolase and photolyase - Marcia S. Osburne; Brianne M. Holmbeck; Jorge Frias‐Lopez; Robert Steen; Katherine Huang; Libusha Kelly; Allison Coe; Kristin Waraska; Andrew Gagne; Sallie W. Chisholm (Environmental Microbiology, 2010)
Summary Exposure to solar radiation can cause mortality in natural communities of pico‐phytoplankton, both at the surface and to a depth of at least 30 m. DNA damage is a significant cause of death, mainly due to cyclobutane pyrimidine dimer formation, which can be lethal if not repaired. While developing a UV mutagenesis protocol for the marine cyanobacterium Prochlorococcus , we isolated a UV‐hyper‐resistant variant of high light‐adapted strain MED4. The hyper‐resistant strain was constitutively upregulated for expression of the mutT ‐ phrB operon, encoding nudix hydrolase and photolyase, both of which are involved in repair of DNA damage that can be caused by UV light. Photolyase (PhrB) breaks pyrimidine dimers typically caused by UV exposure, using energy from visible light in the process known as photoreactivation. Nudix hydrolase (MutT) hydrolyses 8‐oxo‐dGTP, an aberrant form of GTP that results from oxidizing conditions, including UV radiation, thus impeding mispairing and mutagenesis by preventing incorporation of the aberrant form into DNA. These processes are error‐free, in contrast to error‐prone SOS dark repair systems that are widespread in bacteria. The UV‐hyper‐resistant strain contained only a single mutation: a 1 bp deletion in the intergenic region directly upstream of the mutT ‐ phrB operon. Two subsequent enrichments for MED4 UV‐hyper‐resistant strains from MED4 wild‐type cultures gave rise to strains containing this same 1 bp deletion, affirming its connection to the hyper‐resistant phenotype. These results have implications for Prochlorococcus DNA repair mechanisms, genome stability and possibly lysogeny.

The genome and structural proteome of an ocean siphovirus: a new window into the cyanobacterial ‘mobilome’ - Matthew B. Sullivan; Bryan Krastins; Jennifer L. Hughes; Libusha Kelly; Michael Chase; David Sarracino; Sallie W. Chisholm (Environmental Microbiology, 2009)
Summary Prochlorococcus , an abundant phototroph in the oceans, are infected by members of three families of viruses: myo‐, podo‐ and siphoviruses. Genomes of myo‐ and podoviruses isolated on Prochlorococcus contain DNA replication machinery and virion structural genes homologous to those from coliphages T4 and T7 respectively. They also contain a suite of genes of cyanobacterial origin, most notably photosynthesis genes, which are expressed during infection and appear integral to the evolutionary trajectory of both host and phage. Here we present the first genome of a cyanobacterial siphovirus, P‐SS2, which was isolated from Atlantic slope waters using a Prochlorococcus host (MIT9313). The P‐SS2 genome is larger than, and considerably divergent from, previously sequenced siphoviruses. It appears most closely related to lambdoid siphoviruses, with which it shares 13 functional homologues. The ∼108 kb P‐SS2 genome encodes 131 predicted proteins and notably lacks photosynthesis genes which have consistently been found in other marine cyanophage, but does contain 14 other cyanobacterial homologues. While only six structural proteins were identified from the genome sequence, 35 proteins were detected experimentally; these mapped onto capsid and tail structural modules in the genome. P‐SS2 is potentially capable of integration into its host as inferred from bioinformatically identified genetic machinery int , bet , exo and a 53 bp attachment site. The host attachment site appears to be a genomic island that is tied to insertion sequence (IS) activity that could facilitate mobility of a gene involved in the nitrogen‐stress response. The homologous region and a secondary IS‐element hot‐spot in Synechococcus RS9917 are further evidence of IS‐mediated genome evolution coincident with a probable relic prophage integration event. This siphovirus genome provides a glimpse into the biology of a deep‐photic zone phage as well as the ocean cyanobacterial prophage and IS element ‘mobilome’.